Вогнище землетрусу: моделювання, визначення параметрів і використання - Малицький, Д.В.; Муйла, О.О.; Павлова, А.Ю.; Грицай, О.Д.; Коваль, Ю.П.; Обідіна, О.О. (Геоінформатика, 2016)
Для моделювання поширення сейсмічних хвиль у неоднорідному середовищі — горизонтально-шаруватій пружній структурі — застосовано матричний метод. Отримані співвідношення для полів переміщень на вільній поверхні шаруватого півпростору використано для визначення тензора сейсмічного моменту як функції часу через виділення тільки прямих P- і S-хвиль. На підставі розробленої методики для точкового джерела запропоновано визначення посування по розриву (зміщення на розриві) для розподіленого джерела. Таким чином, чисельний метод на основі розв’язання прямої задачі використано з метою інверсії спостережуваних сигналів для компонент тензора сейсмічного моменту і часової функції джерела землетрусу, а також визначення посування по розриву. Подано розв’язання оберненої задачі щодо визначення механізму вогнища землетрусу методом інверсії хвильових форм у випадку обмеженої кількості станцій та графічним методом, а також для встановлення площини розриву. Фокальний механізм визначено графічним методом і методом інверсії сигналу для подій, що відбулися біля с. Угля (24.10.2012 р., 03:13:40.50), і в провінції Альберта, Канада (09.08.2014 р., 15:28:51.00). Побудовані механізми вогнищ місцевих землетрусів, а також параметри для розподіленого джерела можуть бути використані для вивчення та дослідження напружено-деформованого стану гірських масивів у регіонах з низькою сейсмічністю. Для моделирования распространения сейсмических волн в неоднородной среде, которая представлена в виде горизонтально-слоистой упругой структуры, применен матричный метод. Полученные соотношения для полей перемещений на свободной поверхности слоистого полупространства использованы с целью определения тензора сейсмического момента как функции времени путем выделения только прямых P- и S-волн. На основе разработанной методики для точечного источника предложено определение подвижки по разрыву (смещения на разрыве) для распределенного источника. Таким образом, численный метод на основе решения прямой задачи использован с целью инверсии наблюдаемых сигналов для компонент тензора сейсмического момента и временной функции очага землетрясения, а также для подвижки по разрыву. Представлены решения обратной задачи по определению механизма очага землетрясения методом инверсии волновых форм в случае ограниченного количества станций и графическим методом, а также для установления плоскости разрыва. Фокальный механизм определен графическим методом и методом инверсии сигнала для событий, которые произошли возле с. Угля (24.10.2012 р., 03:13:40.50, φ₀ = 48,1676°, λ₀ = 23,6525°, h = 4,5 км, ML = 2,43) и в провинции Альберта, Канада (09.08.2014 р. 15:28:51.00, φ₀ = 52,1646°, λ₀ = -115,256°, h = 4,9, ML = 3,8). Определенные в работе механизмы очагов местных землетрясений, а также параметры для распределенного источника могут быть использованы для изучения и исследования напряженно-деформированного состояния горных массивов в регионах с низкой сейсмичностью. Purpose. The purpose of the article is to determine focal mechanisms using a graphical method and the method of inverse waveforms with a limited number of stations, and to construct a fault plane for distributed sources. Design/methodology/approach. A matrix method was used for modelling seismic waves in a heterogeneous medium, which is represented as a horizontal layered elastic structure. The obtained expression for the displacement fields on the free surface on the layered half-space was used to determine the seismic moment tensor as a function of time by providing only direct P- and S-waves. We determined the slip for distributed sources using the methodology for a point source. So, to determining the components of the moment tensor, a source time function and a slip numerical method based on direct problem solution were used for inversion signals.
Findings. We present the solution of the inverse problem to determine the focal mechanism using inverse waveforms for a limited number of stations and with graphic methods, as well as to determine the fault plane. Focal mechanism was defined by a graphic method and signal inversion for the event that took place near village Uhlya (24.10.2012, 03:13:40.50, φ₀ = 48,1676°, λ₀ = 23,6525°, h = 4,5 km, ML = 2,43), and also for the events that took place at Alberta, Canada (09.08.2014. 15:28:51.00, φ₀ = 52,1646, λ₀ = -115,256, h = 4,9, ML = 3,8).
Practical value/implications. We propose to apply graphic method to determine the focal mechanisms for events in the Carpathian region. We describe the method of inverse waveforms for a limited number of stations to determine focal mechanisms. The method for determining the fault plane using data from one or more stations is presented. The obtained focal mechanisms of local earthquakes and the parameters for distributed sources can be used to study stressed strained state of the mountain ranges in the regions with low seismic activity, which is important for Transcarpathian region.